THE IMPORTANCE OF MAP OF INSEMINATOR LOCATIONS AND BALI COW POPULATION IN IMPROVING ARTIFICIAL INSEMINATION SERVICES IN BADUNG REGENCY - Bargawa, I G. R; Oka, I G.L.; Suyadnya, I P. (E-Journal Of Animal Science Udayana University; Vol 3, No 2, Tahun 2014, 2014)
Artificial insemination services on Bali cattle in Badung Regency have not been optimum up to 2012 since the number and distribution of the inseminators have not been evaluated in relation to the cows population in the villages of this regency. The aims of this study were to create a map of Bali cow population and locations of inseminators in order to improve the artificial insemination services in this regency. Data of Bali cattle population base on the result of census in 2011 were used in this study and interview on the inseminators was carried out to find out the existing problems in the field. Mapping of the location of the inseminators and cow population in the villages of Badung Regency was done using Geographic Positioning System (GPS). The results of the survey showed that inseminators were not well distributed according to the number of cows available in each village or district of Badung regency, and this regency still needs a total of 22 inseminators to optimize the application of artificial inseminators. This was shown by the map of inseminators and cows population in the villages of Badung Regency. Other factors such as skill of the inseminators were needed to be improved, addition of inseminator facilities particularly motorcycles were needed to be added since 57.69% of the inseminators have not got motorcycles for their duties in the field. It was concluded that the map of the inseminator locations and population of cows in Badung regency as well as addition of motorcycles and improvement of the inseminator skills to optimize the implication artificial insemination program were needed in this regency.
Keywords: Map, Inseminator location, cow population and artificial insemination